Organization and decision - Luhmann, Niklas 1927-1998 (Cambridge University Press, 2018)
Organization theory: the classical constructions -- Organization as an autopoietic system -- Membership and motives -- The paradox of decision-making -- Time relations -- Uncertainty absorption -- Decision premises -- Decision programs -- Personnel -- The organization of organization -- Structural change: the poetry of reform and the reality of evolution -- Technology -- Organization and society -- Self-description -- Rationality -- Conclusion: theory and practice
Includes bibliographical references and index
Translation from the German language edition: "Organisation und Entscheidung" by Niklas Luhmann. Wiesbaden: VS Verlag, 2011.
Keywords: Soziales System; Autopoiese; Entscheidung; Organisationstheorie; Kommunikation; Organisation; Systemtheorie; Organizational behavior; Organizational change; Organizational effectiveness